2000
DOI: 10.1093/jpepsy/25.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Identity in Adolescent Survivors of Childhood Cancer

Abstract: Data were interpreted to suggest that the foreclosed identity status may serve a protective function in assisting survivors to cope with the stressors of the cancer experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
3
44
0
1
Order By: Relevance
“…Madan-Swain et al [28] have investigated identity in adolescent survivors of childhood cancer, using the Extended Objective Measure of Ego Identity Status-2 for this purpose. This instrument classifies individuals into four identity states: diffusion (no exploration, no commitment), foreclosure (no exploration, commitment), moratorium (exploration, no commitment), and achievement (exploration, commitment).…”
Section: Socio-behavioral Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Madan-Swain et al [28] have investigated identity in adolescent survivors of childhood cancer, using the Extended Objective Measure of Ego Identity Status-2 for this purpose. This instrument classifies individuals into four identity states: diffusion (no exploration, no commitment), foreclosure (no exploration, commitment), moratorium (exploration, no commitment), and achievement (exploration, commitment).…”
Section: Socio-behavioral Adjustmentmentioning
confidence: 99%
“…Levin Newby et al [26] concluded that more family cohesiveness was associated with more behavioral problems. According to Madan-Swain et al [28], family functioning characterized by greater levels of conflict was positively associated with foreclosed identity status, which is an identity state of commitment to goals and beliefs without having experienced a period of questioning or reflection.…”
Section: Family Functioningmentioning
confidence: 99%
“…Other studies [11][12][13] that have examined adolescent cancer survivors diagnosed with posttraumatic stress disorder (PTSD) also have demonstrated the impact of maternal influences. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), 14 PTSD, a type of anxiety disorder triggered by experiencing or witnessing a traumatic event, can include distressing symptoms such as intrusive thoughts, avoidant behavior associated with triggers related to the trauma, and signs of heightened arousal.…”
mentioning
confidence: 99%
“…Moreover, adolescent PTSD and greater levels of family conflict were shown to be associated with a foreclosed identity status (which typically takes the form of adopting a family member's identity) in adolescent survivors of childhood cancer. 12 According to MadanSwain et al 12 this suggests that PTSD symptoms may further create a more rigid, 'rule-bound' family functioning style, due to a fear of retraumatization which, in turn, minimizes the chances of the adolescent developing his/her identity.…”
mentioning
confidence: 99%
“…В невеликому числі випадків присутня коморбідна психічна патологія, що має місце до розвитку онкологічного захворювання, або ж провокована ним [17].…”
Section: результати дослідженняunclassified